The institutional inertia in regional integration processes: the path dependence method applied to the cases of the European Union and Mercosur - Szucko, Angélica Saraiva (2017)
This article aims to demonstrate, through the historical method of path dependence, the development of integration processes of the European Union and MERCOSUR and their consequent institutional inertia as well as to compare their difficulties and advances. Firstly, a brief overview of the theories of regional integration will be presented. Secondly, using a historical-comparative analysis of path dependence, the critical junctures, the institutional reproduction process and the reactive sequences of each case will be identified. Finally, the resulting institutional inertia of these integration processes will be evaluated.